The Influence of Iron Lathe Waste Addition to the Flexural Strength of Galvanized Fiber Concrete - Rachmawati Suci Khasanah; Karmila Achmad; Masrul Huda (Nusantara Civil Engineering Journal, 2002)
Galvanized wire and iron lathe are alternative fiber types in fiber concrete mixes. Galvanized wire has flexural properties, no corrosion it is relatively inexpensive, while iron lathe waste is known to increase the flexural strength of beams. The study uses 5 cm long galvanized wire with 2% cement by weight and uses iron lathe waste. The purpose of this study is to obtain the value of the flexural strength of the beam.The test specimens used were 12 samples with a variation of 3 pieces each, with the code for normal concrete specimens (NA-NB-NC), 2% galvanized fiber concrete (2A-2B-2C), galvanized fiber concrete with iron lathe variation 10% (10A-10B-10C), galvanized fiber concrete with iron lathe variation 14% (14A-14B-14C). The test was carried out when the concrete was 28 days old with a plan of 22.5 MPa concrete quality.The test results are the average value of the flexural strength of normal concrete is 0.900 MPa, the flexural strength of galvanized fiber concrete is 0.975 MPa, the flexural strength of galvanized fiber concrete with the addition of waste iron lathe with a variation of 10% is 1.425 MPa, variations 14% is 1,125 MPa. The highest percentage of flexural strength increase ratio for normal concrete is 10% variation of 58.333% and for galvanized fiber concrete is 10% variation of 46.154%.